Low hydrostatic pressure promotes functional homeostasis of nucleus pulposus cells through the TRPV4/CRT/FA complex axis - Hu, Junxian; Zhu, Yibo; Pang, Zeyu; Li, Xiaoxiao; Zhang, Huilin; Li, Xiangwei; Gao, Yongjian; Wang, Yiyang; Li, Pei; Zhou, Qiang (Frontiers in Medicine, 2025)
The low hydrostatic pressure in the intervertebral disc plays a crucial role in maintaining the homeostasis of the disc environment, particularly in supporting the physiological functions of nucleus pulposus cells (NPCs). However, the underlying mechanisms remain poorly understood. TRPV4, a baroreceptor in the intervertebral disc, is primarily responsible for converting extracellular pressure signals into intracellular chemical signals. Upon activation, TRPV4 facilitates the influx of calcium ions, thereby regulating the physiological behavior of NP cells. Calreticulin (CRT), an endoplasmic reticulum retention protein, performs various physiological functions, including the regulation of intracellular calcium levels. CRT also exhibits distinct roles depending on its subcellular localization. In this study, we observed that under low hydrostatic pressure, TRPV4 activation and subsequent calcium influx led to an increase in CRT synthesis and a significant rise in its cytosolic expression. This was followed by the depolymerization of focal adhesion (FA) complexes, primarily consisting of FAK and integrin β1, which resulted in an increase in collagen type II (Col II) and a decrease in collagen type I (Col I). These changes in extracellular matrix (ECM) composition helped maintain the physiological function of NP cells. Furthermore, overexpression of CRT enhanced the ability of NP cells to resist partial functional damage caused by high hydrostatic pressure. Taken together, our findings suggested that low hydrostatic pressure enhanced NP cell function by regulating the TRPV4/CRT/FA complex signaling axis.